The effect of enterprise risk management (ERM) on firm value in manufacturing companies listed on Indonesian Stock Exchange year 2010-2013 - Iswajuni Iswajuni; Arina Manasikana; Soegeng Soetedjo (Emerald Publishing Limited, 2018)
The purpose of this paper is to identify the effect of enterprise risk management (ERM) with firm size, ROA and managerial ownership as control variables on firm value that is proxied by Tobin’s Q.Population of this research was manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2010–2013. The used method in this research is multiple linear regression-ordinary least square and hypotheses testing using t-test to test the regression coefficients with level of significance of 5 percent.The results showed that ERM, ROA and size of the company have a significant positive effect on the firm value. While the managerial ownership has a significant negative effect on the firm value.The results showed that firm value increases as ERM, ROA and size of the company improves. While the managerial ownership has a significant negative effect on the firm value.